Segmentation of brain tumor images using in vivo spectroscopy, relaxometry and diffusometry by magnetic resonance - M. Martín-Landrove (Revista Mexicana de Física, 2006)
A new methodology is developed for the segmentation of brain tumor images using information obtained by different magnetic resonance techniques such as in vivo spectroscopy, relaxometry and diffusometry. In vivo spectroscopy is used as a sort of virtual biopsy to characterize the different tissue types present in the lesion (active tumor, necrotic tissue or edema and normal or non-affected tissue). Due to the fact that in vivo spectroscopy information lacks the spatial resolution for treatment considerations, this information has to be combined or fused with images obtained by relaxometry and diffusometry with excellent spatial resolution. Some segmentation schemes are presented and discussed, using the high spatial resolution techniques individually or combined. The results show that segmentation done in this way is highly reliable for the application of future therapies such as radiosurgery or radiotherapy.